ANALISIS PENGARUH STORE IMAGE PERCEPTION DAN STORE BRAND PRICE IMAGE TERHADAP STORE BRAND PURCHASE INTENTION DENGAN PERCEIVED RISK SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Konsumen Supermarket Super Indo Majapahit) - Jannah, Miftakhul; Indriyatni, Lies; Widowati, Maduretno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
Store brands are a form of strategy used in competing for retailers in a market that is increasingly competitive. Based on previous research, there are several factors that influence buying interest, namely Store Image Perception, Perceived Risk, and Store Brand Price Image. This study aims to see the influence of the influence of Store Image Perception, Perceived Risk, and Store Brand Price Image Image Intention on Super Indo Majapahit supermarkets. The research method used in the study Statistics Product and Service Solutions (SPSS) for Windows 16.0 with regression analysis and path analysis for the mediating variables. The technique used to study the data is a survey using a structured questionnaire. The population and samples in this study were visitors or buyers of Super Indo Majapahit supermarkets with the results of 89 respondents who can be used in this study. The results of the study indicate that Store Image Perception has a significant positive effect on Store Brand Purchase Intention in Super Indo Majapahit consumers. Store Brand Price Image has a significant positive effect on Store Brand Purchase Intention for Super Indo Majapahit consumers. Store Image Perception has a significant negative effect on Perceived Risk on Super Indo Majapahit consumers. Store Brand Price Image has a significant negative effect on Perceived Risk on Super Indo Majapahit consumers. Perceived Risk has a significant negative effect on Store Brand Purchase Intention for Super Indo Majapahit consumers. Store Brand Price Image significantly influences Store Brand Purchase Intention through Perceived Risk mediation at Super Indo Majapahit. All hypotheses have a significant effect except Store Image Perception which has no significant effect on Store Brand Purchase Intention through the mediation of Perceived Risk at Super Indo Majapahit because tstatistic (1.591) < ttable (1.663).Keywords: store brand, image, price, risk, purchase intention.